Local Tumor Control Affects Survival of Patients with Osteosarcoma and Ewing Sarcoma - Suryawan, Nur; Syifannisa, Ilma; Anantha, I Made Brahmystha Valqy (Majalah Kedokteran Bandung, 2025)
Osteosarcoma and Ewing sarcoma are the most common primary malignant bone tumors in children. This study aimed to analyze the characteristics of osteosarcoma and Ewing sarcoma patients at Dr. Hasan Sadikin General Hospital, Bandung, Indonesia, from 2020 to 2023 and compare the one-year survival rates between patients who underwent complete treatment (surgery for local tumor control and chemotherapy) and those who received chemotherapy alone. This study used a descriptive-analytical observational design with a retrospective approach by reviewing electronic medical records from the Indonesian Pediatric Cancer Registry (IPCAR). A total of 44 osteosarcoma patients and 14 Ewing sarcoma patients who met the inclusion criteria were included. The majority of patients were boys (osteosarcoma=61.36%; Ewing sarcoma=64.29%), with a mean age of 13.5 years for osteosarcoma and 9.1 years for Ewing sarcoma. Osteosarcoma was most commonly found in the femur and tibia (90.92%), whereas Ewing sarcoma was primarily located in the axial region (71.43%). Most patients underwent chemotherapy without local tumor control (osteosarcoma=61.36%; Ewing sarcoma=57.14%). The analysis revealed a significant difference in one-year survival between patients who received local tumor control combined with chemotherapy and those who underwent chemotherapy alone (osteosarcoma p=0.000; Ewing sarcoma p=0.010). In conclusion, local tumor control significantly improves one-year survival in both tumor types.